In Vitro Inhibition Assessment of Acetyl Cholinesterase by Mahabhutarava Ghrta - MP, Nima; M, Jithesh; MP, Parvatheedevy (Asian Journal of Pharmaceutical Research and Development, 2023)
Psychiatric disorders can make a huge negative impact not only to the patient but also to the family and his society. Schizophrenia is one among them that may lead to alteration in cognition and conation. Ayurveda considers the usage of ghrta preparations as the best strategy for the management of such psychiatric ailments. In the present study, a ghrta yoga, Mahabhutaravaghrta which had been in practise for the management of Schizophrenia and other psychiatric conditions was selected and an invitro inhibition assessment of Acetylcholinesterase has been planned. If inhibition is identified in the ghrta, it can justify the clinical efficacy of the drug in the patients.